ANANKASTIK PERSONALITY DISORDER IN SCHIZOPHRENIA PARANOID PATIENT: A CASE REPORT - Damarnegara ..; A. A. Ngr. Andika (Universitas Udayana, 2014)
Anankastik personality disorder is a health problem that can disturb the activities of person and can accompany a variety of other mental health problems. The patient in thiscase is a patient with an anankastik or obsessive compulsive personality disorder withthe axis I diagnoses is Paranoid Schizophrenia and was given haloperidol 2x5mg, buthave not done psychotherapy because the patient has not been cooperative. Theprognosis is dependent on patient compliance in taking medication and controls for thesetting of the dose, and the support of her family.